Safety and Therapeutic Efficacy of Thymoquinone-Loaded Liposomes against Drug-Sensitive and Drug-Resistant Acinetobacter baumannii - Khaled S. Allemailem; Abdullah M. Alnuqaydan; Ahmad Almatroudi; Faris Alrumaihi; Aseel Aljaghwani; Habibullah Khalilullah; Hina Younus; Arif Khan; Masood A. Khan (MDPI AG, 2021)
In the present study, we investigated the activity of free thymoquinone (TQ) or liposomal thymoquinone (Lip-TQ) in comparison to standard antibiotic amoxicillin (AMX) against the drug-sensitive and drug-resistant Acinetobacter baumannii. A liposomal formulation of TQ was prepared and characterized and its toxicity was evaluated by analyzing the hematological, liver and kidney function parameters. TQ was effective against both drug-sensitive and drug-resistant A. baumannii as shown by the findings of drug susceptibility testing and time kill kinetics. Moreover, the therapeutic efficacy of TQ or Lip-TQ against A. baumannii was assessed by the survival rate and the bacterial load in the lung tissues of treated mice. The mice infected with drug-sensitive A. baumannii exhibited a 90% survival rate on day 30 post treatment with Lip-TQ at a dose of 10 mg/kg, whereas the mice treated with AMX (10 mg/kg) had a 100% survival rate. On the other hand, the mice infected with drug-resistant A. baumannii had a 70% survival rate in the group treated with Lip-TQ, whereas AMX was ineffective against drug-resistant A. baumannii and all the mice died within day 30 after the treatment. Moreover, Lip-TQ treatment effectively reduced the bacterial load in the lung tissues of the mice infected with the drug-sensitive and drug-resistant A. baumannii. Moreover, the blood of the mice treated with Lip-TQ had reduced levels of inflammation markers, leukocytes and neutrophils. The results of the present study suggest that Lip-TQ may prove to be an effective therapeutic formulation in the treatment of the drug-sensitive or drug-resistant A. baumannii infection as well.